A new subgenus, Australixodes n. subgen. (Acari: Ixodidae), for the kiwi tick, Ixodes anatis Chilton, 1904, and validation of the subgenus Coxixodes Schulze, 1941 with a phylogeny of 16 of the 22 subgenera of Ixodes Latreille, 1795 from entire mitochondrial genome sequences - Barker, Stephen C.; Kelava, Samuael; Heath, Allen C. G.; Seeman, Owen D.; Apanaskevich, Dmitry A.; Mans, Ben J.; Shao, Renfu; Gofton, Alexander W.; Teo, Ernest J. M.; Byrne, Andrew F.; Ito, Takuya; Tan, Craig J.; et al. (Zootaxa, 2023)
A new subgenus, Australixodes n. subgen., is described for the kiwi tick, Ixodes anatis Chilton, 1904. The subgenus Coxixodes Schulze, 1941 is validated for the platypus tick, Ixodes (Coxixodes) ornithorhynchi Lucas, 1846, sister group of the subgenus Endopalpiger Schulze, 1935. A phylogeny from mitochondrial genomes of 16 of the 22 subgenera of Ixodes (32 spp.) indicates, for the first time, the relationships of the subgenera of Ixodes Latreille, 1795, the largest genus of ticks.